Thidiazuron combined with cyclanilide modulates hormone pathways and ROS systems in cotton, increasing defoliation at low temperatures - Shu, Hongmei; Sun, Shangwen; Wang, Xiaojing; Chen, Jian; Yang, Changqin; Zhang, Guowei; Han, Huanyong; Li, Zhikang; Liang, Ting; Liu, Ruixian (Frontiers in Plant Science, 2024)
Low temperatures decrease the thidiazuron (TDZ) defoliation efficiency in cotton, while cyclanilide (CYC) combined with TDZ can improve the defoliation efficiency at low temperatures, but the mechanism is unknown. This study analyzed the effect of exogenous TDZ and CYC application on cotton leaf abscissions at low temperatures (daily mean temperature: 15°C) using physiology and transcriptomic analysis. The results showed that compared with the TDZ treatment, TDZ combined with CYC accelerated cotton leaf abscission and increased the defoliation rate at low temperatures. The differentially expressed genes (DEGs) in cotton abscission zones (AZs) were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses to compare the enriched GO terms and KEGG pathways between the TDZ treatment and TDZ combined with CYC treatment. TDZ combined with CYC could induce more DEGs in cotton leaf AZs at low temperatures, and these DEGs were related to plant hormone and reactive oxygen species (ROS) pathways. CYC is an auxin transport inhibitor. TDZ combined with CYC not only downregulated more auxin response related genes but also upregulated more ethylene and jasmonic acid (JA) response related genes at low temperatures, and it decreased the indole-3-acetic acid (IAA) content and increased the JA and 1-aminocyclopropane-1-carboxylic acid (ACC) contents, which enhanced cotton defoliation. In addition, compared with the TDZ treatment alone, TDZ combined with CYC upregulated the expression of respiratory burst oxidase homologs (RBOH) genes and the hydrogen peroxide content in cotton AZs at low temperatures, which accelerated cotton defoliation. These results indicated that CYC enhanced the TDZ defoliation efficiency in cotton by adjusting hormone synthesis and response related pathways (including auxin, ethylene, and JA) and ROS production at low temperatures.